Where are all the surgeons in clinical academia? - McVeigh, J; Smillie, R; Wiberg, A; Furniss, D (Royal College of Surgeons of England, 2022)
Introduction: High-quality research into surgical disease will benefit surgical patients. Whereas nearly one-fifth of National Health Service (NHS) England consultants are surgeons, less than 5% of the government’s health research funding supports surgical research.